Makna Kias dalam 'Penyangkalan' oleh For Revenge: Sebuah Eksplorasi Emosi dan Ketidakpastian - Raudatul Jannah; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research analyzes the figurative meanings in the lyrics of "Penyangkalan" by For Revenge, an Indonesian rock band, which reflects the emotional experiences of individuals trapped in toxic relationships. Previous studies indicate that figurative language in music can enhance understanding of trauma and psychological defense mechanisms. Yet, there remains a gap in literature examining the relationship between song lyrics and emotional experiences. This study aims to identify and analyze the use of figurative language in "Penyangkalan" lyrics and how these elements convey emotional messages related to toxic relationships. Using a descriptive qualitative approach with text analysis, the study examines the song lyrics through theme identification, pattern recognition, and meaning analysis, validated through triangulation techniques. The findings reveal that the lyrics employ various language styles, including metaphors, personification, and repetition, to portray the complexity of emotions and trauma in toxic relationships, ultimately serving as a mirror for emotional experiences while providing insights into broader psychological impacts in a social context.